Association between temporomandibular disorders in people with anxiety (Research, Society and Development, 2022)
The temporomandibular joint is one of the most complex structures in the human skull. When there is any change in its structure, it is usually called temporomandibular disorder. This pathology has a multifactorial etiology with great influence of psychic aspects, such as anxiety. This study aims to carry out a literature search verifying the association of temporomandibular disorders as a consequence of anxiety. To this end, a search was carried out in the literature, in database sites, such as Scielo, Pubmed and Google Scholar, seeking the most relevant information that was convenient to the subject of the study. People with anxiety disorders tend to discharge greater muscle tension in the oral region, resulting in losses such as bruxism, dental wear and TMD, with women being the most affected gender. Individuals with temporomandibular disorders may suffer from constant headaches, affecting their quality of life. The professional must know the characteristics and peculiarity of the pathology to make the correct diagnosis. Multiprofessional treatment is the most recommended.